Total Synthesis and Structural Revision of Laurefurenynes A and B. Issue 38 (19th August 2013) - Holmes, Michael T.; Britton, Robert
<x xml:space="preserve">Abstract</x> Structural reassignment: A total synthesis of the proposed structure of (−)‐laurefurenyne A has been accomplished that relies on organocatalytic aldehyde α‐chlorination and a flexible chlorohydrin‐based strategy for stereocontrolled access to the bis‐tetrahydrofuran core of the natural product. Analysis of incongruities between the 1H NMR spectra of synthetic and natural material led to a configurational reassignment for the natural product, which was also confirmed by total synthesis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>